Policy Implications for the Green Bank Development in the Context of Global Climate Change - Nga Phan Thi Hang (Ital Publication, 2022)
With the global financial crisis in 2008, climate change, and the COVID-19 pandemic, most countries worldwide have re-thought their organization and operating models in their financial systems, including the banking system. In Vietnam, sustainable economic development has become an essential need in the long term. However, sustainable development requires a balance between economic growth and environmental protection. Therefore, Vietnam has chosen to develop a green economy, in which